Rasio Keuangan sebagai Prediktor Bank Bermasalah di Indonesia - Titik Aryati; Hekinus Manao (The Indonesian Journal of Accounting Research, 2013)
This research is aimed to examine the possible association between bank financial ratios derived from CAMEL concept and the failures of  a number of banks in Indonesia during the monetary crisis period. Seven independent variables were used in the analysis, i.e. capital adequacy ratio (CAR), return on risked assets (RORA),  net profit margin (NPM), return on assets (ROA), operating cost to operating revenue, net call-money liabilities to current assets, and loan to deposit ratio (LDR). Tests were undertaken using the univariate model approach and the multivariate discriminant analysis.The result shows five significant financial ratios to affect the probability of a bank to go for bankrupt in a five year horizon. The ratio are CAR, RORA, ROA, net call-money liabilities to current assets, and LDR. However, when testing the association one year prior to bank failure, this study reveals RORA, ROA, LDR, operating cost to operating revenue, and call-money liabilities to currents assets to be significant for bankruptcy prediction in banking industry in Indonesia.Meanwhile, the discriminant analysis includes only two bank financial ratios – RORA and LDR – in the model for predicting bank failures. The classification results based on these cut-off Z-score values were able to predict bank failures in Indonesia at the accuracy rates of 82 %, 69.1 %, 65.3% within 1, 2, and 3 year horizons respectively, a far better result compared to the naïve prediction.